Equipment Quality Control - Sa dos Reis, Claudia (2015)
Mammography equipment must be evaluated to ensure that images will be of acceptable diagnostic quality with lowest radiation dose. Quality Assurance (QA) aims to provide systematic and constant improvement through a feedback mechanism to address the technical, clinical and training aspects [1, 2]; Quality Control (QC), in relation to mammography equipment, comprises a series of tests to determine equipment performance characteristics. The introduction of digital technologies promoted changes in QC tests and protocols and there are some tests that are specific for each manufacturer [2]. Within each country specific QC tests should be compliant with regulatory requirements and guidance [1]. Ideally, one mammography practitioner should take overarching responsibility for QC within a service, with all practitioners having responsibility for actual QC testing. All QC results must be documented to facilitate troubleshooting, internal audit and external assessment [3, 4].